Developing Students’ Awareness of Recount Text Patterns (The Practical Reflection of Using Burger-shaped Graphic Organizer) - Nurhasanah Halim; Susilawati Susilawati; Arrizqi Ramadhan; Siti Yulidhar Harunasari; Retno Dwigustini; Fitri Fajar Ratri (Jurnal Scientia, 2022)
Writing in the context of EFL has been viewed as a challenging task, for students are required to compose their text structurally and accurately. The recent research aims at investigating how the burger-shaped graphic organizer (GO) assisted students in developing their awareness of recount text pattern, and how its teaching was reflected. The recent research employed action research. The participants consisted of 20 students in the second grade of junior high school. The data were collected using a test, interview, and observation. The data were then analyzed using the following steps: data reduction, display, and verification. The findings signified that, first, to develop students’ awareness of recount text patterns, the teacher can incorporate genre analysis and use the burger-shaped GO as the supplementary resource to assist students’ awareness of recount text pattern. Second, the students gave positive feedback on the use of the burger -shaped GO in their writing class, so that the teacher might consider using it in teaching another genre. Further studies is highly suggested for detailed investigation of how the burger-shaped GO might enhance students’ critical thinking